IMPORTANCE OF RESEARCH HLA ANTIBODIES CLASS I AND II, AND MICA ANTIBODIES IN KIDNEY TRANSPLANTATION - M. Sh. Khubutia; N. V. Borovkova; N. V. Doronina; A. V. Pinchuk; I. V. Alexandrova (Вестник трансплантологии и искусственных органов)
The purpose of this study was to investigate the occurrence of HLA and MICA antibodies in patients from the waiting list for kidney transplantation and their influence on the course of post-transplant period. Determination of HLA antibodies class I and II, and MICA antibodies was performed on a platform of Luminex (xMAP-tech- nology) using sets LABScreen ONE LAMBDA (U.S.). A total of 156 patients from the waiting list for kidney transplantation. Revealed the presence of HLA and MICA antibodies in the serum of 31.4% of patients. Regraf- ted patients increased the content of antibodies to the antigens of HLA system was noted in 88.2% of cases, 47% met the combination of antibodies to the I, II classes and MICA. In patients awaiting first kidney transplantation, HLA and MICA antibodies were determined in 23.7% of cases. The presence of pretransplant HLA and MICA antibodies had a significant influence on the course of post-transplant period. Patients with the presence of HLA and MICA in 50% of cases delayed graft function. Sessions of plasmapheresis can reduce the concentration of HLA and MICA antibodies on average by 61.1%.